2020
DOI: 10.3389/fimmu.2020.01877
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Galectins by Pathogens for Infection

Abstract: Galectins are glycan-binding proteins which are expressed by many different cell types and secreted extracellularly. These molecules are well-known regulators of immune responses and involved in a broad range of cellular and pathophysiological functions. During infections, host galectins can either avoid or facilitate infections by interacting with host cells-and/or pathogen-derived glycoconjugates and less commonly, with proteins. Some pathogens also express self-produced galectins to interfere with host immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 154 publications
(209 reference statements)
0
18
0
Order By: Relevance
“…Emerging evidences emphasize that in some cases, these galectin-glycan interactions may benefit the pathogen by providing the ability to adhere, by enhancing uptake as well as by modulating immune effector functions. 32 T. whipplei is an intracellular bacterium which replicates in alternatively activated macrophages. Although, it has been shown that T. whipplei glycoproteins are important for bacterial replication in macrophages, their contribution during the infection process is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidences emphasize that in some cases, these galectin-glycan interactions may benefit the pathogen by providing the ability to adhere, by enhancing uptake as well as by modulating immune effector functions. 32 T. whipplei is an intracellular bacterium which replicates in alternatively activated macrophages. Although, it has been shown that T. whipplei glycoproteins are important for bacterial replication in macrophages, their contribution during the infection process is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that external addition of soluble Gal-1 and Gal-3 either enhance or inhibit cell entry of some pathogens. 32 For example, soluble Gal-1 enhances C. trachomatis uptake in a dose-dependent manner in vitro 34 while for T. cruzi , cell adhesion is increased with the addition of soluble Gal-3. 37 In contrast, addition of Gal-1 inhibits the internalization of Dengue virus and Nipah Virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is the case with many immunoregulatory proteins, galectin expression is modulated with EC activation in response to inflammatory mediators, pathogen exposure, and injury (22,(33)(34)(35). A concentration-dependent increase in expression of galectin-9 mRNA and protein was observed in vitro following treatment of primary HUVEC with double-stranded RNA viral mimetic, polyinosinic-polycytidylic acid [poly(I:C)], a Toll-like receptor (TLR) 3 ligand (33,34).…”
Section: Regulation Of Galectin Expression In Inflammationmentioning
confidence: 99%
“…Galectins are a family of small soluble proteins able to recognize glycans containing a β‐ d ‐galactopyranoside structural motif [1–4] . They are found both intracellularly and extracellularly, where they are involved in many physiological and pathological functions, such as metabolism, immunity, inflammation and cancer progression [4–8] …”
Section: Introductionmentioning
confidence: 99%